Breast cancer and exposure to aircraft, road, and railway-noise: a case–control study based on health insurance records - Hegewald, Janice; Schubert, Melanie; Wagner, Mandy; Dröge, Patrik; Prote, Ursel; Swart, Enno; Möhler, Ulrich; Zeeb, Hajo; Seidler, Andreas (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'Aircraft, road, and rail traffic noise can cause sleep disturbances. Since night work and shorter sleep durations have been linked to increased risks of breast cancer, we examined if 24-hour, or day- or night-time traffic noise exposure may also increase the risk of breast cancer. ' ' METHODS ': 'To investigate the noise-related risks of breast cancer, the pseudonymized insurance records of three large statutory health companies (2005–2010) for women aged ≥40 years living in the region surrounding the Frankfurt international airport were analyzed with address-specific acoustic data representing aircraft, road, and rail-traffic noise. Noise exposure among women with incident breast cancer (N=6643) were compared with that of control subjects (N=471 596) using logistic regression and adjusting for age, hormone replacement therapy, education and occupation (only available for 27.9%), and a regional proportion of persons receiving long-term unemployment benefits as an ecological indicator of socioeconomic level. Analyses were also stratified according to estrogen receptor (ER) status. ' ' RESULTS ': 'An increased odds ratio (OR) was observed for ER negative (ER-) tumors at 24-hour aircraft noise levels 55–59 dB [OR 55–59 dB 1.41, 95% confidence interval (CI) 1.04–1.90] but not for ER positive (ER+) breast cancers (OR 55–59 dB 0.95, 95% CI 0.75–1.20). Clear associations between road and rail traffic noise were not observed. ' ' CONCLUSIONS ': 'The results indicate increased aircraft noise may be an etiologic factor for ER- breast cancers. However, information regarding potential confounding factors was largely unattainable. Further research is required to understand how environmental noise may be involved in the pathogenesis of ER- breast cancers.
Keywords: aircraft; aircraft noise; breast cancer; breast neoplasm; cancer; environment; epidemiology; estrogen; estrogen receptor; exposure; railway; railway noise; risk; road; road noise; traffic noise; transportation